An Evaluation of the Effects of Agro-tourism Development - Wojciechowska, Jolanta (Turyzm/Tourism, 2006)
The effects of agro-tourism development, as perceived by local inhabitants and tourists, are presented by means of two-dimensional pyramids. These perceptions differ as In the case of tourists the pyramid is inverted. The article also attempts to evaluate the effects of agro-tourism development in statistical and dynamic terms, and indicates patterns in the costs and benefits to local communities.